PERAN IMPLEMENTASI KURIKULUM DALAM MENINGKATKAN RELIGIUSITAS MAHASISWA - Susilana, Rudi; Ihsan, Helli; Hadiapurwa, Angga (Universitas Pendidikan Indonesia, 2020)
Abstract. The religiosity of students on campus tends to decrease during their education on campus because of the secularization of knowledge on campus. Thus, the role of the campus is very important in increasing student’s religiosity. The religiosity of students can be influenced by the campus by developing religious courses such as Islamic Religious Education and also through scientific courses that are widely studied in religious contexts. The problem is the extent to which the ability of scientific lecturers to study religious knowledge in the context of science which is taught in the course. This research uses narrative and explanatory analysis. The result of this research is that there is no curriculum that has been studied in detail and comprehensively in public universities in the world so that religiosity becomes the core basis for the preparation.Abstrak. Religiositas mahasiswa di kampus cenderung mengalami penurunan selama menjalani pendidikan di kampus karena sekulerisasi keilmuan yang diajrkan di kampus. Peran kampus dengan demikian sangat penting dalam meningkatkan religiositas mahasiswa. Religisositas mahasiswa bisa dipengaruhi oleh kampus dengan cara mengembangkan mata kuliah keagamaan seperti Pendidikan Agama Islam dan juga bisa melalui mata kuliah keilmuan yang banyak mengkaji keilmuan itu dalam konteks keagamaan. Problermnya adalah sejauhmana kemampuan dosen dalam mengkaji ilmu agama dalam konteks keilmuan yang diajarkannya dalam mata kuliah. Penelitian ini menggunakan analisis naratif dan eksplanatori. Hasil penelitian ini adalah bahwa belum ada kurikulum yang dikaji secara detail dan komprehensif pada universitas umum di dunia ini agar religiositas menjadi dasar inti dalam penyusunan tersebut.